EFFECTS OF NEEM, Azadirachta indica, SEEDS’ FILTRATE ON HATCHING, MORTALITY, AND INFECTIVITY OF ROOT-KNOT NEMATODE, Meloidogyne javanica - Sudirman 1 (CROP AGRO, Scientific Journal of Agronomy, 2012)
ABSTRACT Effect of neem (Azadirachta indica) seeds’ filtrate on hatching, mortality, and infectivity of Meloidogyne javanica was investigated. Six concentrations of filtrate (1, 4, 10, 25, 50, and 100 g/L) were evaluated on hatching of M. javanica for 3, 7 and 14 days. Mortality of M. javanica was studied by exposing J2 in four concentrations of filtrate (10, 25, 50, and 100 g/L) for 24 hours. Then infectivity of nematode was investigated after incubated J2 in 25-g/L filtrate for 1, 6, 12, and 24 hours. All experiments were completely randomized designed and, where appropriate, data were analyzed with analysis of variance followed by honestly significant different test at 5% significant level. Research results show that filtrate inhibited egg hatch with inhibition gradually increased with time and was concentration-dependent. Exposure to 1 g/L filtrate caused least inhibition of J2 hatching, and 50- and 100- g/L filtrate produced 100% inhibition at all times. Second-stage juvenile mortality was concentration-dependent and 100% mortality was achieved by exposure to 100-g/L, 50-g/L, and 25- g/L filtrates within 9, 22, and 24 hours, consecutively. Infectivity of J2 decreased by 50, 73, and 84% after nematodes had been exposed to 25 g/L filtrate for 6, 12, and 24 hours, respectively. ABSTRAK Pengaruh filtrat biji nimba (Azadirachta indica) terhadap tetasnya telur, mortalitas, dan infektifitas Meloidogyne javanica telah diteliti. Filtrat dengan enam konsentrasi (1, 4, 10, 25, 50, dan 100 g/L) diuji pengaruhnya pada tetasnya telur M. javanica selama 3, 7, dan 14 hari. Mortalitas nematoda diteliti dengan memaparkan J2 pada empat konsentrasi filtrat (10, 25, 50, dan 100 g/L) selama 24 jam. Infektifitas nematoda diuji setelah J2diinkubasi dalam filtrat 25-g/L selama 1, 6, 12, dan 24 jam. Semua percobaan dirancang secara acak lengkap dan, dimana perlu, data dianalisa dengan analisis keragaman dilanjutkan dengan uji beda nyata jujur pada taraf nyata 5%. Hasil penelitian menunjukkan bahwa filtrat menghambat penetasan telur dengan penghambatan yang meningkat seiring waktu dan konsentrasi. Pemaparan pada filtrat 1-g/L menyebabkan hambatan tetas yang paling sedikit, dan filtrat 50- dan 100-g/L menghambat penetasan 100% pada setiap pengamatan. Mortalitas J2 tergantung pada konsentrasi filtrat dan mortalitas 100% dicapai dengan filtrat 100-g/L, 50-g/L, and 25- g/L masing-masing setelah pemaparan selama 9, 22, dan 24 jam. Infektifitas J2 berkurang 50, 73, and 84% setelah nematoda dipaparkan pada filtrat 25-g/L masing-masing selama 6, 12, dan 24 jam.